Distance travelled to hospital for emergency laparotomy and the effect of travel time on mortality: cohort study. Issue 5 (23rd June 2020) - Salih, Tom; Martin, Peter; Poulton, Tom; Oliver, Charles M; Bassett, Mike G; Moonesinghe, S Ramani
Abstract : Objectives: To evaluate whether distance and estimated travel time to hospital for patients undergoing emergency laparotomy is associated with postoperative mortality. Design: National cohort study using data from the National Emergency Laparotomy Audit. Setting: 171 National Health Service hospitals in England and Wales. Participants: 22 772 adult patients undergoing emergency surgery on the gastrointestinal tract between 2013 and 2016. Main outcome measures: Mortality from any cause and in any place at 30 and 90 days after surgery. Results: Median on-road distance between home and hospital was 8.4 km (IQR 4.7–16.7 km) with a median estimated travel time of 16 min. Median time from hospital admission to operating theatre was 12.7 hours. Older patients live on average further from hospital and patients from areas of increased socioeconomic deprivation live on average less far away. We included estimated travel time as a continuous variable in multilevel logistic regression models adjusting for important confounders and found no evidence for an association with 30-day mortality (OR per 10 min of travel time=1.02, 95% CI 0.97 to 1.06, p=0.512) or 90-day mortality (OR 1.02, 95 % CI 0.97 to 1.06, p=0.472). The results were similar when we limited our analysis to the subgroup of 5386 patients undergoing the most urgent surgery. 30-day mortality: OR=1.02 (95% CI 0.95 to 1.10, p=0.574) and 90-day mortality: OR=1.01 (95% CI 0.94 to 1.08, p=0.858). Conclusions: In the UK NHS, estimated travel time between home and hospital was not a primary determinant of short-term mortality following emergency gastrointestinal surgery.